2016
DOI: 10.1371/journal.pone.0166282
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially-Associated Transcriptional Remodelling in a Distinct Genomic Subtype of Colorectal Cancer Provides a Plausible Molecular Basis for Disease Development

Abstract: The relevance of specific microbial colonisation to colorectal cancer (CRC) disease pathogenesis is increasingly recognised, but our understanding of possible underlying molecular mechanisms that may link colonisation to disease in vivo remains limited. Here, we investigate the relationships between the most commonly studied CRC-associated bacteria (Enterotoxigenic Bacteroides fragilis, pks+ Escherichia coli, Fusobacterium spp., afaC+ E. coli, Enterococcus faecalis & Enteropathogenic E. coli) and altered trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…The ability of Fusobacterium species to elicit an immune response, in particular to recruit T-cells, is reflected in the immunological signature seen in the CMS1 tumours. Our targeted qPCR analysis of F. nucleatum that showed an increased abundance associated with CMS1, also reflects the findings of two studies that found that Fusobacterium was associated with a CRC subtype characterised by CpG island methylation, MSI and inflammatory signatures [15], and higher prevalence in right-sided tumours [46], all hallmarks of CMS1 [6].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ability of Fusobacterium species to elicit an immune response, in particular to recruit T-cells, is reflected in the immunological signature seen in the CMS1 tumours. Our targeted qPCR analysis of F. nucleatum that showed an increased abundance associated with CMS1, also reflects the findings of two studies that found that Fusobacterium was associated with a CRC subtype characterised by CpG island methylation, MSI and inflammatory signatures [15], and higher prevalence in right-sided tumours [46], all hallmarks of CMS1 [6].…”
Section: Discussionsupporting
confidence: 85%
“…Comparison of faecal microbiomes from CRC patients and healthy controls [9][10][11][12] has identified particular bacterial species that are enriched in CRC, and analysis of tumour, adenoma, and matched normal tissue from the same patients found that changes in local communities of potentially interacting bacterial taxa are associated with different disease states [12,13]. Correlations between particular cancer mutations and changes in microbial communities, and transcriptional remodelling associated with specific bacteria have recently been described in CRC [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…So, to establish a direct, causal connection between the gut microbiome and CRC development, we must determine whether and how microbes alter mutation rates, gene methylation, chromatin structure, and/or non-coding RNA expression in CECs. Several epidemiological studies have associated specific bacteria in the gut with tumors that are characterized by DNA hypermethylation [36][37][38][39] or by specific mutational patterns [40], strengthening the hypothesis that gut microbes have a role in CRC development through their effects on the genome and epigenome of CECs.…”
Section: Not Yet Identifiedmentioning
confidence: 92%
“…In particular, it had been wellaccepted that specific bacterial species played at least some roles in the initiation and/or progression of colorectal cancer. And up-regulation of Reg3A was found in the tumors with highlevel colonization by Fusobacterium, a kind of colorectal cancerassociated bacteria (33).…”
Section: Up-regulation Of Reg3a In Gastrointestinal Cancermentioning
confidence: 98%